Integrating dye-intercalated DNA dendrimers with electrospun nanofibers: a new fluorescent sensing platform for nucleic acids, proteins, and cells1. Issue 17 (7th May 2015) - Wang, Huaming; Tang, Wei; Wei, Hejia; Zhao, Yan; Hu, Shichao; Guan, Yan; Pan, Wei; Xia, Bin; Li, Na; Liu, Feng
<x xml:space="preserve">Abstract</x> A fluorescent dye-intercalated DNA dendrimer probe was integrated with electrospun nanofibers to create an amplified sensing platform for disease-related species.